Galactic bulge preferred over dark matter for the Galactic centre gamma-ray excess. (May 2018) - Macias, Oscar; Gordon, Chris; Crocker, Roland; Coleman, Brendan; Paterson, Dylan; Horiuchi, Shunsaku; Pohl, Martin
Abstract An anomalous gamma-ray excess emission has been found in the Fermi Large Area Telescope data1 covering the centre of the Galaxy2, 3 . Several theories have been proposed for this 'Galactic centre excess'. They include self-annihilation of dark-matter particles4, an unresolved population of millisecond pulsars5, an unresolved population of young pulsars6, or a series of burst events7 . Here, we report on an analysis that exploits hydrodynamical modelling to register the position of interstellar gas associated with diffuse Galactic gamma-ray emission. We find evidence that the Galactic centre excess gamma rays are statistically better described by the stellar over-density in the Galactic bulge and the nuclear stellar bulge, rather than a spherical excess. Given its non-spherical nature, we argue that the Galactic centre excess is not a dark-matter phenomenon but rather associated with the stellar population of the Galactic bulge and the nuclear bulge. New hydrodynamical models are used to fit the Fermi-LAT data of the Galactic centre and show that the excess γ-ray emission of the region is better fitted by a non-spherical shape, indicating that it is not caused by dark-matter-related phenomena.